Experimental duration determines the effect of arbuscular mycorrhizal fungi on plant biomass in pot experiments: A meta-analysis - Qin, Mingsen; Li, Lei; Miranda, Jean‐Pascal; Tang, Yun; Song, Bo; Oosthuizen, Maria Kathleen; Wei, Wangrong (Frontiers in Plant Science, 2022)
Arbuscular mycorrhizal fungi (AMF) play various important roles in promoting plant growth. Numerous environmental and evolutionary factors influence the response of plants to AMF. However, the importance of the individual factors on the effects of AMF on plant biomass is not clearly understood. In this study, a meta-analysis using 1,640 observations from 639 published articles related to the influence of AMF on the plant shoot, root, and total biomass was performed; 13 different experimental setting factors that had an impact on the influence of AMF and their importance were quantitatively synthesized. The meta-analysis showed that AMF had positive effects on the plant shoot, root, and total biomass; moreover, the experimental duration, plant root-to-shoot ratio (R/S), AMF root length colonization, plant family, pot size, soil texture, and the soil pH all influenced the effects of AMF on the shoot, root, and total biomass. In addition, the plant root system and plant functional type had impacts on the effect of AMF on shoot biomass; AMF guild also impacted the effect of AMF on root biomass. Of these factors, the experimental duration, plant R/S, and pot size were the three most important predicting the effects of AMF on the plant shoot, root, and total biomass. This study comprehensively assessed the importance of the different factors that influenced the response of plants to AMF, highlighting that the experimental duration, plant R/S, and pot size should be taken into consideration in pot experiments in studies of the functions of AMF. Multiple unfavorable factors that may obscure or confound the observed functions of AMF should be excluded.